Pengembangan Kurikulum Pondok Pesantren - Chusnul Chotimah, Khoirun Nisa' (INOVATIF: Jurnal Penelitian Pendidikan, Agama dan Kebudayaan, 2020)
Boarding schools as one of the Islamic education institutions in Indonesia have actually had the opportunity to create quality human resources with a record of boarding schools are able to adapt to globalization that is happening by without leaving the character of his order. Among the components of the staple in a pesantren is; (1) Huts (dorm dormitories), (2) Mosques, (3) students, (4) Teaching classical books/Yellow books, (5) Kiai and Ustadz (6) Madrasah/School and (7) system of values (SALAF/Traditional-khalaf/modern) as the spirit of every pesantren. In certain pesantren there is also in the Madrasah or school with all the completeness (combination). Curriculum education Pesantren is the materials of Islamic religious education in the form of pesantren activities, knowledge and experiences that are intentionally and systematically given to students in order to achieve the objectives of Islamic religious education. The education curriculum is a tool to achieve the objectives of Islamic religious education. The scope of education material is: Qur'an and Hadith, faith, morality, FIQH/worship and history, in other words, the scope of education on the trend of harmony, harmony and balance of human relations with God, Self, fellow man, other creatures and the environment.